Determinants of banks' engagement in loan securitization - Christina E. Bannier; Dennis N. Hänsel (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2006)
This paper provides new insights into the nature of loan securitization. We analyze the use of collateralized loan obligation (CLO) transactions by European banks from 1997 to 2004 and try to identify the influence that various firm-specific and macroeconomic factors may have on an institution's securitization decision. We find that not only regulatory capital arbitrage under Basel I has been driving the market. Rather, our results suggest that loan securitization is an appropriate funding tool for banks with high risk and low liquidity. It may also have been used by commercial banks to indirectly access investment-bank activities and the associated gains.
Keywords: G21; 330; Securitization; credit risk transfer; collateralized loan obligations